Critical reflections on the concept of maintenance - Lind, Hans; Muyingo, Henry (International Journal of Strategic Property Management, 2012)
The purpose of the paper is to critically evaluate the conceptual distinction between investment and maintenance. The study starts from a number of definitions in the literature and discusses these from the perspective of standard investment theory. The article argues that the standard concept of investment covers all relevant decisions and also puts the focus on the future consequences of decision and not whether it restores an earlier standard or not. The research implications are that investment and maintenance planning need to be analysed together and that the distinction between investment and maintenance is uninteresting from a decision theoretic and resource allocation perspective. The practical implications of the article are that what usually is called investment planning and maintenance planning need to be integrated. The originality in the paper lies primarily in the questioning of the usefulness of the concept of maintenance in a dynamic age where the relation to earlier characteristics and functions becomes less and less interesting. The role of the maintenance concept is now primarily related to various administrative systems (accounting, taxation) but is not so relevant from a forward looking resource allocation perspective.First Publish Online: 19 Jun 2012